REFOMASI POLITIK, DEMOKRASI, DAN INTEGRASI NASIONAL - Nasikun, Nasikun (Jurnal Bestari, 2001)
?We have brought state and individual very close, largely through destruction or weakening of ties which once lay intermediate, providing the state with institutitional checks upon its expansion and the individual with sources of security? (Robert Nisbet, 1979: 71).